Knowledge on primary and secondary prevention of asthma among caregivers of asthmatic children admitted to paediatric wards in Gampaha District - Niranjala Perera; Chrisantha Abeysena (College of Community Physicians of Sri Lanka, 2019)
Introduction: Asthma is considered to be one of the major public health problems. The accurate knowledge of caregiver on asthma is important for the management.   Objectives: To describe the knowledge on primary and secondary prevention of asthma among caregivers of asthmatic children admitted to the paediatric wards in the district of Gampaha   Methods: A descriptive cross-sectional study was carried out among 577 caregivers of inward asthmatic children. Pre-tested interviewer- and self-administered questionnaires were used to assess the knowledge on asthma. The grand score of knowledge on asthma was calculated out of 34. The 75th percentile value was considered to differentiate 'good' knowledge from 'poor' knowledge. Multiple logistic regression was applied to determine the factors associated with poor knowledge on asthma. Results were expressed in adjusted odds ratio (aOR) and 95% confidence interval (CI).   Results: The mean score for knowledge on asthma was 20.6 (SD=4.42) ranging from 7 to 30. Among the caregivers, 369 (64%) had poor knowledge on asthma. Low educational level of the caregiver (aOR=2.48; 95% CI=1.59, 3.86) and being under prophylaxis treatment for less than one year (aOR=2.49; 95% CI=1.50, 4.13) were the determinants of poor knowledge on asthma.   Conclusions: Majority of the caregivers' knowledge on asthma was poor. The caregivers' low educational level and shorter duration of prophylaxis treatment for the children were associated with poor knowledge on asthma.